Perspectives on deciphering mechanisms underlying plant heat stress response and thermotolerance - Bokszczanin, Kamila L.; Fragkostefanakis, Sotirios; Bostan, Hamed; Bovy, Arnaud; Chaturvedi, Palak; Chiusano, Maria L.; Firon, Nurit; Iannacone, Rina; Jegadeesan, Sridharan; Klaczynskid, Krzysztof; Li, Hanjing; Mariani, Celestina; et al. (Frontiers in Plant Science, 2013)
Global warming is a major threat for agriculture and food safety and in many cases the negative effects are already apparent. The current challenge of basic and applied plant science is to decipher the molecular mechanisms of heat stress response and thermotolerance in detail and use this information to identify genotypes that will withstand unfavorable environmental conditions. Nowadays X-omics approaches complement the findings of previous targeted studies and highlight the complexity of heat stress response mechanisms giving information for so far unrecognized genes, proteins and metabolites as potential key players of thermotolerance. Even more, roles of epigenetic mechanisms and the involvement of small RNAs in thermotolerance are currently emerging and thus open new directions of yet unexplored areas of plant heat stress response. In parallel it is emerging that although the whole plant is vulnerable to heat, specific organs are particularly sensitive to elevated temperatures. This has redirected research from the vegetative to generative tissues. The sexual reproduction phase is considered as the most sensitive to heat and specifically pollen exhibits the highest sensitivity and frequently an elevation of the temperature just a few degrees above the optimum during pollen development can have detrimental effects for crop production. Compared to our knowledge on heat stress response of vegetative tissues, the information on pollen is still scarce. Nowadays, several techniques for high-throughput X-omics approaches provide major tools to explore the principles of pollen heat stress response and thermotolerance mechanisms in specific genotypes. The collection of such information will provide an excellent support for improvement of breeding programs to facilitate the development of tolerant cultivars. The review aims at describing the current knowledge of thermotolerance mechanisms and the technical advances which will foster new insights into this process.